Electrochemical cell lysis of gram-positive and gram-negative bacteria: DNA extraction from environmental water samples. (1st April 2020) - Wang, Siwen; Zhu, Yanzhe; Yang, Yang; Li, Jing; Hoffmann, Michael R.
Abstract: Cell lysis is an essential step for the nucleic acid-based surveillance of bacteriological water quality. Recently, electrochemical cell lysis (ECL), which is based on the local generation of hydroxide at a cathode surface, has been reported to be a rapid and reagent-free method for cell lysis. Herein, we describe the development of a milliliter-output ECL device and its performance characterization with respect to the DNA extraction efficiency for gram-negative bacteria ( Escherichia coli and Salmonella Typhi) and gram-positive bacteria ( Enterococcus durans and Bacillus subtilis ). Both gram-negative and gram-positive bacteria were successfully lysed within a short but optimal duration of 1 min at a low voltage of ∼5 V. The ECL method described herein, is demonstrated to be applicable to various environmental water sample types, including pond water, treated wastewater, and untreated wastewater with DNA extraction efficiencies similar to a commercial DNA extraction kit. The ECL system outperformed homogeneous chemical lysis in terms of reaction times and DNA extraction efficiencies, due in part to the high pH generated at the cathode surface, which was predicted by simulations of the hydroxide transport in the cathodic chamber. Our work indicates that the ECL method for DNA extraction is rapid, simplified and low-cost with no need for complex instrumentation. It has demonstrable potential as a prelude to PCR analyses of waterborne bacteria in the field, especially for the gram-negative ones. Graphical abstract: An electrochemical lysis device has been developed for DNA extraction of gram-positive and gram-negative bacteria from varied environmental samples. Image 1 Highlights: An electrochemical cell lysis (ECL) device was developed based on local high pH at cathode surface. Different bacteria were successfully lysed with an optimal duration of 1 min at a low voltage of ∼5 V. Various environmental water samples were demonstrated with high DNA extraction efficiencies.